(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Patients with recent myocardial infarction have an increased incidence of impaired fasting glucose (IFG) and new-onset diabetes. There is a clear relationship between elevated fasting glucose during acute myocardial infarction and increased mortality and morbidity risk. Objective: To find out the impact of fasting glycaemia as a predictor of outcome of patients with acute myocardial infarction. Methods: A total of 102 patients with acute myocardial infarction of first attack were selected according to inclusion and exclusion criteria. Fifty-one patients with acute myocardial infarction having fasting hyperglycaemia were enrolled as case group and another 51 patients with acute myocardial infarctions having fasting euglycaemia were enrolled as control group. Results: Among the diabetic patients, acute left ventricular failure (ALVF) developed in 22 (68.8% ), arrhythmias in 5 (16.6%) and cardiovascular mortality in 8 (25.0% ) patients ; it was 7 (36.8%), 4 (21.1 %) and 4 (21.1 %) respectively in IFG patients; and 7 (13.7%) ,4 (7.8%) and 2 (3.9%) respectively in euglycaemia patients. Acute left ventricular failme and 30 days CV mortality significantly differed among the groups (p<0.001 and p=0.015 respectively). But no significant difference in arrhythmias (p=-0.284). Conclusions: The patients of impaired fasting glucose (IFG) and diabetes mellitus both were predictor for in hospital heart failure (ALVF) and 30-day cardiovascular mortality as compared to euglycaemia.